Aligning Local Interventions with Global and Constitutional Frameworks: A Comprehensive Policy Review for Strengthening Climate Resilience and Economic Security in Balochistan through Targeted Water Management and Climate-Smart Agriculture - Javed, Adnan Ahmad; Nauman, Muhammad Mustafa (Indonesian Journal Publisher, 2025)
Balochistan, Pakistan’s driest province, faces severe water shortages, long droughts, and heatwaves, threatening its farming economy. Current water policies, shaped by the Indus Waters Treaty, do not address the groundwater crisis or adaptation needs, worsening poverty and food insecurity. This review aims to assess community-driven changes in water management and climate-smart agriculture to build resilience and economic security. It focuses on improving climate resilience while aligning with Pakistan's constitutional commitments and international agreements, such as the Paris Agreement and the UN SDGs. The analysis shows that decentralized solutions like drip irrigation, rainwater harvesting, drought-resistant crops, and community-led governance can significantly reduce water use by up to 90%, boost crop yields by 15-40%, and lower financial losses. To break the cycle of vulnerability, policymakers must shift from large, centralized projects to community-focused approaches, integrating climate-resilient microfinance into provincial planning